Polymer derived gel-like preceramic precursor of core-shell silicon oxycarbide ceramic for robocasting. Issue 17 (1st December 2019) - Hu, Lung-Hao; Wang, Yu-Kai; Wang, Sheng-Chang
Abstract: The conventional techniques for 3D printing ceramic parts are the ceramic powder laser sintering and lithography process that are usually costly in equipment and materials. A low-cost technique for robocasting ceramic has been developed via polysilazane preceramic precursor incorporated with nano γ-alumina powders to form a gel-like preceramic precursor with the aim to be used as the raw material for robocasting ceramic parts. The gel-like preceramic precursor is simply extruded for shaping by CAD design with the self-incorporated robocasting machine, and then pyrolyzed the shaped gel-like preceramic precursor at 700, 850 and 950 °C, respectively to transform from a polymeric composite to core-shell silicon oxycarbide ceramic composite that has been characterized by XRD representing an amorphous silicon oxycarbonitride structure coating on the surface of nano γ-alumina. The Vickers hardness of the core-shell silicon oxycarbide ceramic is about HV 266–300 that is two times higher than that of 7000 series aluminum alloy.